The Influence of Water Deficit on Dehydrin Content in Callus Culture Cells of Scots Pine - Natalia Korotaeva; Vladimir Shmakov; Vadim Bel’kov; Daria Pyatrikas; Sofia Moldavskaya; Igor Gorbenko (Plants, 2024)
Under a water deficit, the protective proteins known as dehydrins (DHNs) prevent nonspecific interactions in protein and membrane structures and their damage, in addition to playing an antioxidant role. The DHNs of a widespread xerophytic species Scots pine (Pinus sylvestris L.) have been poorly studied, and their role in resistance to water deficits has not been revealed. In this paper, we have expanded the list of DHNs that accumulate in the cells of Scots pine under the conditions of water deficits and revealed their relationship with the effects of water deficits. In this investigation, callus cultures of branches and buds of Scots pine were used. A weak water deficit was created by adding polyethylene glycol to the culture medium. Under the conditions of a water deficit, the activity of catalase and peroxidase enzymes increased in the callus cultures. A moderate decrease in the total water content was correlated with a decrease in the growth rate of the callus cultures, as well as with an increase in the activity of lipid peroxidation. The accumulation of Mr 72, 38, and 27 kDa DHNs occurred in the callus cultures of buds, and the accumulation of Mr 72 and 27 kDa DHNs positively correlated with the lipid peroxidation activity. An increase in the content of DHNs was observed in cultures that differed in origin, growth indicators, and biochemical parameters, indicating the universality of this reaction. Thus, previously undescribed DHNs were identified, the accumulation of which is caused by water deficiency and is associated with manifestations of oxidative stress in the kidney cells of Scots pine.